Economic democracy : the politics of feasible socialism - Archer, Robin (Oxford : Clarendon Press ; New York : Oxford University Press, 1995)
The author argues that by pursuing economic democracy, socialism can return to the heart of political life in advanced capitalist countries. He demonstrates that there is both a moral case for economic democracy and a feasible strategy for achieving it.
Includes bibliographical references and index.
Keywords: Employee ownership; Socialism; Corporate state; Management -- Employee participation